Hippocampal place cell sequences differ during correct and error trials in a spatial memory task - Chenguang Zheng (Nature Portfolio, 2021)
Here the authors compare place cell sequence coding during correct and error trials in a spatial memory task. Sequences coded paths that were longer and more temporally compressed during correct trials and developed a bias to replay paths to a goal location during rest periods of correct but not error trials.